Cosmic Disintegration in Béla Tarr’s Late Films: An Aesthetic Approach to Nihilism - Gutiérrez-Suárez, Gustavo (Cinémas)

(untitled) (Cinémas, 2025)
The present article aims to study certain pivotal features in the nihilistic aesthetics of Béla Tarr. To achieve this goal, I address three cinematographic images observed in Tarr’s late films from an aesthetic perspective: crowds of people, animals and climatic phenomena. Firstly, the article provides a comparative review of the aesthetic qualities of crowds. Secondly, animals and climatic phenomena are analyzed focusing on their meaningful interactions with humans. This comparative-analytical study reveals two salient aesthetic themes: crowds, animals and climatic phenomena comprise the entirety of a cosmos in disintegration; moreover, these cinematographic images are being coalesced by the continuity principle that defines such cosmos. Tarr’s aesthetic approach captures a cosmos that is being shaped and held together by the organic interconnectedness between humans, animals and climatic phenomena, while they slowly undergo the same process of annihilation. This article engages in a dialogue with Stellino’s philosophical study of nihilism in Tarr, Handelmann’s anthropological theory of cosmos in Western ideology, and Rancière’s essays on the poetics of Béla Tarr.